PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS GAME EDUKASI PADA MATERI OPERASI PERKALIAN - Muhammad Rifki Ananta; Nurmayanti; Syamsunir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop and determine the feasibility of an educational game-based learning media as an evaluation tool for multiplication material. The ADDIE model is used in this research design which has five stages: analysis, design, development, implementation, and evaluation. Testing was carried out by media and material validators to determine validity, while trials were carried out by student respondents to determine practicality. The media validation results got a score of 72% which is in the valid category, while the material validation got a score of 82,9% which is in the very valid category. Meanwhile, the results of student respondents gave an assessment of 85.6%, which shows that this game is very practical to use as a tool for evaluating multiplication material. With positive feasibility results from the three groups, this educational game is proven to have great potential to be used as a learning tool, in this case as an evaluation tool for multiplication material.